Incidence and distribution of amoebic gill disease (AGD) - an epidemiological review - Oldham, TM; Rodger, H; Barbara Nowak (2016)
Amoebic gill disease (AGD), first documented thirty years ago in sea-caged salmonids, is an ever increasing global concern in finfish aquaculture. The result of gill infection by Neoparamoeba perurans, clinical AGD has been observed in fourteen countries distributed across six continents and in fifteen species of finfish. The greatest impacts of AGD have been on farmed Atlantic salmon during the seawater grow-out phase. When left untreated AGD has resulted in up to 80% mortality, and even mild infections reduce production performance and fish welfare. This review summarizes and analyses three decades of AGD research and outbreaks, with focus on the causal triad of pathogen, host and environment. Statement of relevance: This review provides an improved understanding of AGD including practical applications.